2001
DOI: 10.1002/1097-0282(200107)59:1<29::aid-bip1003>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of cross-linked poly(KGGVG), an elastin-like biopolymer

Abstract: Previous studies afforded on peptides and polypeptides containing repetitive sequences of elastin have largely demonstrated that their molecular and supramolecular properties are fully representative of those of tropoelastin, the soluble, linear precursor of elastin itself. In the attempt to synthesize cross‐linked elastin‐mimetic polypeptides, the repeating sequence VGGVG (V: valine; G: glycine), typical of elastin, was modified to incorporate lysine residues, yielding the polymer poly(KGGVG) (K: lysine). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…There are many other variants of ELPs that range from other pentapeptides with the repeat sequences KGGVG [37] or LGGVG [38] to heptapeptides with the sequence LGAGGAG and nonapeptides with the sequence LGAGGAGVL [39]. All of these elastin analogues appear to exhibit elastin-like properties.…”
Section: Elastin-like Polypeptides-elastincontrasting
confidence: 63%
See 1 more Smart Citation
“…There are many other variants of ELPs that range from other pentapeptides with the repeat sequences KGGVG [37] or LGGVG [38] to heptapeptides with the sequence LGAGGAG and nonapeptides with the sequence LGAGGAGVL [39]. All of these elastin analogues appear to exhibit elastin-like properties.…”
Section: Elastin-like Polypeptides-elastincontrasting
confidence: 63%
“…Also, because ELPs can be designed at the molecular level and genetically synthesized, unique properties can be introduced by incorporating other biologically active peptide sequences. Examples can be found of ELP hydrogels that are formed by irradiation [246][247][248], photoinitiation [249], amine-reactive chemical crosslinking [37,68,[250][251][252][253][254][255][256][257][258][259][260], and enzymatic crosslinking by tissue transglutaminase [261]. The hydrogels have been successfully used for cartilage and intervertebral disc tissue repair, small-diameter vascular grafts, urinary bladders, stem cell matrices, neural guides, stem cell sheets, and post-surgical wound treatment [250][251][252][253][254][255][256][262][263][264].…”
Section: Chemically Crosslinked Elastin-based Hydrogelsmentioning
confidence: 99%
“…To explore further the role of the lysine residues in the interaction of GTA with the VP1 capsid protein of enteroviruses, the sequence of the protein was determined in 15 echovirus prototype strains (serotypes 1,3,4,5,7,13,14,15,19,20,24,26,29,31, and 33). The amino acid sequences were aligned with each other and with that of coxsackievirus B3, used as a reference (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing GTA virucidal activity against isolates and reference strains of poliovirus 1 and echovirus 25, we also observed significant intertypic and intratypic differences (6,7). Numerous reports investigating the process of binding between GTA and various proteins and enzymes have shown that only the ε-amino group of lysine reacts to any significant extent with GTA (8,16,17,20). In light of these findings, we made the assumption that the differences previously observed between enterovirus strains were related to variations in the locations of lysine residues in the capsid proteins, in particular in externalized regions of the VP1 protein.…”
mentioning
confidence: 99%
“…Generally, synthetic soluble elastins that can be used as biomaterials, including tropoelastin [19][20][21][22] and elastin-like peptides [23][24][25][26][27], do not have the cross-linked structures seen in native elastin. Although elastin extracted from an organism has a high possibility of exhibiting native biological properties for VSMC, the manner in which elastin containing cross-linked structures affects VSMCs is unclear.…”
Section: Introductionmentioning
confidence: 99%